New sheriff in town: A quad model approach to examining the consequences of selecting a qualified lead independent directors - Hasija, Dinesh; Ellstrand, Alan; Ridge, Jason W.; Johnson, Jon (Strategic Management Journal, 2025)
Abstract Research Summary The lead independent director (LID) position was adopted primarily to increase the efficiency of the monitoring function of the board. However, evidence of whether and how LIDs influence board monitoring has been limited. We apply and test the theoretical quad model in the context of the LID to examine whether selecting a qualified LID helps improve monitoring within the board. We argue that when a board appoints a qualified LID, it improves overall board monitoring, along with board meeting facilitation and interpersonal interactions between the board and shareholders. Using a sample of US firms, we find that firms that appoint qualified LIDs tend to have lower levels of corporate misconduct, better board meeting attendance, and fewer shareholder proposals. Managerial Summary This study explores the impact of selecting a qualified lead independent director (LID) on corporate governance, highlighting practical benefits for firms that prioritize strong board leadership. Our findings show that appointing a well‐qualified LID can enhance board effectiveness by reducing incidents of corporate misconduct, improving board meeting attendance, and decreasing shareholder activism. These results underscore the importance of careful LID selection as a strategic move to strengthen governance, ensure robust oversight, and improve communication with stakeholders. This research provides actionable insights for boards seeking to bolster governance practices by strategically leveraging the LID position.